Evaluation of Time Performance in Construction Project Implementation: A Case Study of Building X and Building Y - Dian Nazwa Qurratul A'ini; Fathur Rohman Robandi (Journal La Multiapp, 2026)
This study aims to evaluate the implementation of construction project time management in the Building Development Project at RSUD X. The research focuses on analyzing the conformity between planned schedules and actual project execution, identifying time deviations, determining critical path activities, and examining factors causing delays during project implementation. The study employed a descriptive quantitative approach with a case study method. Data were collected through observation, documentation, interviews, project schedules, S-curve data, and weekly progress reports. The analysis was conducted using S-Curve comparison and Critical Path techniques to evaluate project performance in terms of time control. The findings indicate that several project activities experienced delays caused by technical, managerial, and external factors, including material delivery constraints, coordination issues, and field conditions. Critical path analysis identified several key activities that significantly influenced the overall project duration. The study concludes that effective time management, continuous monitoring, and proper scheduling control are essential to minimize delays and improve construction project performance.